How Do Banking Supervisors Deal with Europe-wide Systemic Risk? - Martin Schüler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
The systemic risk potential in the European banking market has increased. Hence, the following questions emerge: Is there a need for a truly European supervisory framework? And, how should a potential European supervisor be organised? This paper evaluates the existing supervisory framework as well as the recent proposal by the Economic and Financial Committee of the EU with respect to the increased Europe-wide systemic risk. We argue that cooperation between national supervisors even in the new framework will not be sufficient for safeguarding financial stability. As a consequence, we argue in favour of a European observatory of systemic risk.
Keywords: G28; 330; banking supervision and regulation; European Union; Bankenaufsicht; EU-Bankrecht; Bankrisiko; Finanzsektor; Wirtschaftliche Instabilität; EU-Staaten; systemic risk